Measuring State Dependence in Individual Poverty Status : Are There Feedback Effects to Employment Decisions and Household Composition? - Martin Biewen (Institute for the Study of Labor (IZA), 2004)
Using a sample of prime-aged men from the German Socio-Economic Panel (GSOEP), this paper examines the effects of past poverty experience on future poverty status, future employment status and household composition. The empirical results suggest that even after controlling for observed and unobserved characteristics, past poverty experience increases the poverty risk of future periods. Moreover, there is evidence that experiencing poverty has a negative effect on future employment behaviour and on household cohesion. Apart from its economic significance, the existence of such feedback effects is interesting from an econometric point of view, as they represent a violation of the strict exogeneity assumption, which is usually invoked in estimating dynamic qualitative response models with unobserved heterogeneity.
Keywords: J12; D31; C33; I32; 330; poverty persistence; dynamic binary response models; correlated random effects; initital conditions; strict exogeneity; Armut; Arbeitsangebot; Privater Haushalt; Schätzung; Deutschland